Implementasi ‘Petualangan Tani Kecil’ pada Siswa Sekolah Dasar untuk Keberlanjutan Pertanian di Masa Depan - Maulana, Fajar Bagus; Madani, Magfirah Ulya; Azis, Riza Rahmat; Fridman, Dzakiriza Dira; Lestari, Lisa; Sinaga, Elizabeth Berliana Paulina; Mufidah, Salsabila Syarifah; Aulia, Titania (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
As time goes by, the younger generation's interest in agriculture is decreasing. Therefore, agricultural learning needs to be carried out among elementary school students, because learning must be instilled from an early age. This activity aims to introduce the concept of sustainable agriculture to elementary school students through practice-based active learning. This service aims to provide an understanding of the importance of sustainable agricultural practices in order to achieve a more sustainable future economically, socially and environmentally. This service approach focuses on learning through simple agricultural practical activities that are relevant to the school environment and students' daily lives. The result of this activity is that elementary school students become more aware of the importance of agriculture in the future. Apart from that, they know how the agricultural process starts from planting, caring for and harvesting.